Carbamoylated Erythropoietin Rescues Autism-Relevant Social Deficits in BALB/cJ Mice - Amaya L. Street; Vedant P. Thakkar; Sean W. Lemke; Liza M. Schoenbeck; Kevin M. Schumacher; Monica Sathyanesan; Samuel S. Newton; Alexander D. Kloth (NeuroSci)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that affects over 2% of the population worldwide and is characterized by repetitive behaviors, restricted areas of interest, deficits in social communication, and high levels of anxiety. Currently, there are no known effective treatments for the core features of ASD. The previous literature has established erythropoietin (EPO) as a promising antidepressant, working as a potent neurogenic and neurotrophic agent with hematopoietic side effects. Carbamoylated erythropoietin (CEPO), a chemically engineered non-hematopoietic derivative of EPO, appears to retain the neuroprotective factors of EPO without the hematologic properties. Recent evidence shows that CEPO corrects stress-related depressive behaviors in BALB/cJ (BALB) mice, which also have face validity as an ASD mouse model. We investigated whether CEPO can recover deficient social and anxiety-related behavioral deficits compared to C57BL/6J controls. After administering CEPO (40 μg/kg in phosphate-buffered saline) or vehicle over 21 days, we analyzed the mice’s performance in the three-chamber social approach, the open field, the elevated plus maze, and the Porsolt’s forced swim tasks. CEPO appeared to correct sociability in the three-chamber social approach task to C57 levels, increasing the amount of time the mice interacted with novel, social mice overall rather than altering the overall amount of exploratory activity in the maze. Consistent with this finding, there was no concomitant increase in the distance traveled in the open field, nor were there any alterations in the anxiety-related measures in the task. On the other hand, CEPO administration improved exploratory behavior in the elevated plus maze. This study marks the first demonstration of the benefits of a non-erythropoietic EPO derivative for social behavior in a mouse model of autism and merits further investigation into the mechanisms by which this action occurs.